Poverty Alleviation through Community Development Zakat in Tanah Datar Regency - Renata, Nadia; Afrimaigus, Riko (Yayasan Mitra Peduli Indonesia, 2022)
The main problem in this study is how to alleviate poverty through the Zakat Community Development (ZCD) in Tanah Datar Regency. The research method is descriptive qualitative. Data were collected through interviews and documentation. The study results indicate that poverty alleviation occurs by increasing the income of mustahiq participants in the (ZCD) program in meeting their daily needs. In addition, poverty alleviation occurs due to the increase in the economic capacity of program participants, which is the result of maximum assistance and education carried out.